The commentaries of Pope Pius II (1458-1464) and the crisis of the fifteenth-century papacy - O'Brien, Emily (Toronto : University of Toronto Press, 2015)
"Written in the mid-fifteenth century, Pope Pius II's Commentaries are the only known autobiography of a reigning pontiff and a fundamental text in the history of Renaissance humanism. In this book, Emily O'Brien positions Pius' expansive autobiographical text within that century's contentious debate over ecclesiastical sovereignty. Presenting the Commentaries as Pius' response to the crisis of authority, legitimacy, and relevance that was engulfing the Renaissance papacy, she shows how the Commentaries function as both an aggressive assault on the papal monarchy's chief opponents and a systematic defense of Pius's own troubled pontificate and his pre-papal career. Illustrating how the language, imagery, and ideals of secular power inform Pius' apologetic self-portrait, The Commentaries of Pope Pius II (1458 1464) and the Crisis of the Fifteenth-Century Papacy demonstrates the role that Pius and his writings played in the evolution of the Renaissance papacy."--
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Pius -- II, -- Pope, -- 1405-1464.; Pius -- II, -- Pope, -- 1405-1464.; Pius -- II, -- Pope, -- 1405-1464.; Commentarii rerum memorabilium (Pius II, Pope); Church history -- Middle Ages, 600-1500 -- Historiography; Popes -- Biography -- History and criticism; Self-perception.; Autobiography; Renaissance -- Italy; RELIGION -- Christianity -- Catholic; Autobiography; Church history -- Middle Ages -- Historiography; Popes -- Biography; Renaissance; Self-perception.; Italy; HISTORY / Ancient / General; Electronic books; Criticism, interpretation, etc